2017
DOI: 10.1037/rep0000126
|View full text |Cite
|
Sign up to set email alerts
|

Developing a measure to assess identity reconstruction in patients with multiple sclerosis.

Abstract: Identity reconstruction provides needed context for understanding adjustment to and living with MS. Examination of the IRAS within a larger sample and in other disease groups can provide additional construct validity evidence. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
1
5
0
2
Order By: Relevance
“…In line with literature, we found that the adjustment to MS was related to both identity satisfaction [19][20][21][22] and self-efficacy 23,25,26 . In particular, the construct of identity seems to be particularly relevant for patients of this age.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In line with literature, we found that the adjustment to MS was related to both identity satisfaction [19][20][21][22] and self-efficacy 23,25,26 . In particular, the construct of identity seems to be particularly relevant for patients of this age.…”
Section: Discussionsupporting
confidence: 90%
“…The illness negatively changes the body functioning and perception, as well as life plans, chances of personal realization and social roles which the individual is engaged in 18 This is particularly dramatic for young people who suddenly perceive themselves as ill and have to reorganize their future perspectives. The few studies that focused on identity and MS among patients with long disease duration found that identity restructuring is a key aspect for the psychosocial adjustment to the illness [19][20][21][22] . Moreover, in our previous study on recently diagnosed patients aged from 18 to 65, it was found that higher identity satisfaction was related to lower depression, higher affective well-being and higher optimism 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means to reorganize their future perspectives and their life goals, taking into account limits and possibilities linked to the illness, and elaborating a self-image that includes the illness, and does not merely coincide with it (Bonino, 2020). Previous studies showed that successfully redefining one's identity is related to lower depressive symptoms and higher quality of life and psychological well-being among MS patients (Irvine et al, 2009;Mozo-Dutton et al, 2012;Tabuteau-Harrison et al, 2016;Calandri et al, 2017aCalandri et al, , 2019Rahn et al, 2017). It is therefore crucial to deepen knowledge about identity, as one of the factors that might promote young adults' adjustment to MS.…”
Section: Introductionmentioning
confidence: 99%
“…Una actitud negativa de los familiares o personas cercanas a la persona con discapacidad puede potenciar a su vez sentimientos negativos en quienes la poseen. Teniendo en cuenta que la identidad está relacionada con la socialización del individuo con su medio, por lo mismo, una interacción negativa dentro de su círculo familiar o social, llevará asimismo a un potencial conflicto de identidad (Hauser-Cram et al, 2009;Nuñez, 2014, Stepleman, et al, 2017. El término discapacidad involucra en sí mismo una dificul-tad, una falta de capacidad u oportunidad, por lo que ya desde que se involucra a este término, se relaciona con la exclusión (Garzón, 2007).…”
Section: Introductionunclassified